Terminal sliding mode based nonlinear control for energy management of fuel cell, battery, and ultracapacitor based plug-in hybrid electric vehicle - Sana Rehman (00000274916); Dr. Adeel Waqas; Dr Iftikhar Ahmad (USPCAS-E, NUST, Islamabad, 2021)
TH-272
Keywords: MS-ESE Thesis MS Thesis